Most consumed foods in Brazil: evolution between 2008-2009 and 2017-2018 - Renata Muniz Rodrigues; Amanda de Moura Souza; Ilana Nogueira Bezerra; Rosangela Alves Pereira; Edna Massae Yokoo; Rosely Sichieri (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVE: To describe the evolution of food consumption by the Brazilian population in 2008-2009 to 2017-2018. METHODS: Data from the National Dietary Surveys of 2008-2009 and 2017-2018 were used. Both surveys estimated food consumption of two non-consecutive days of individuals aged 10 years or older. The first survey collected consumption data from 34,003 individuals through food records; the second, obtained data from 46,164 individuals, through 24-hour recalls. The twenty most frequently reported food groups in the two surveys were identified. The probability of consumption of each food group in the two surveys was estimated according to sex, age and income. This study presents the foods that had a change in the frequency of consumption of 5% or higher between the two surveys. The probability of consumption was corrected for intra-individual variability using the method developed by the National Cancer Institute. RESULTS: Rice, beans, coffee, bread, vegetables and beef remained the staple Brazilian diet, ranking as the six most consumed items in both surveys. Ultra-processed foods such as sweet/stuffed cookies, savory cookies, processed meats and carbonated drinks also remained among the 20 most consumed foods. Trend analyses showed, regardless of gender, age and income range, a decrease in the consumption of rice, beans, beef, bread, fruit, milk and dairy, processed meats and carbonated drinks, and an increase in the consumption of sandwiches. CONCLUSION: The Brazilian diet is still characterized by consumption of traditional foods, such as rice and beans, and by high frequency of consumption of ultra-processed foods, such as cookies and carbonated drinks. However, between the years of 2008-2009 and 20172018, there was a decrease in the consumption of rice, beans, beef, bread, fruit, milk and dairy, processed meats and carbonated drinks, but an increase in the consumption of sandwiches. The results show a decrease in quality in the Brazilian diet.